Chronic diabetic macular oedema, pars plana vitrectomy or combination of PPV and laser? - Synek, Svatopluk; Synková, Monika (Collegium antropologicum, 2008)
Diabetic cystoid macular oedema (DME) is a common cause of visual acuity (VA) decrease. Good anatomical results and VA of pars plana vitrectomy (PPV) in cases of macular hole internal limiting membrane (ILM) peeling leads to usage of this technique in DME. A favorable result even in a case without vitreoretinal traction leads to conclusion that pathogenesis of this disease is different. We analyzed retrospectively 20 eyes from 20 patients with DME that had undergone PPV and ILM peeling. Half of them were laser treated 6 months before surgery. All eyes had an attached posterior hyaloids membrane in the macular region, but without thickening and without traction. Median duration of DME at the time of PPV was 18 months (range 12-24 months). The median preoperative best-corrected VA of 0.4 (range 0.01-1.0), improved to a median postoperative VA of 0.55 (range 0.01-1.0). Ten eyes without preoperative laser coagulation had a median VA improvement of 77%, while 10 eyes with preoperative macular laser treatment had a median VA improvement of 14.8%. In all 20 eyes DME was no longer visible on microscopic examination after a median period of 3 months after PPV. PPV and ILM peeling resulted in the resolution of oedema, with an improvement in VA in the majority of cases. Eyes without preoperative macular photocoagulation had a significantly higher visual improvement than eyes with preoperative laser treatment. A randomized controlled prospective trial of PPV versus laser is needed to determine the role of PPV as a treatment modality for DME.
Keywords: Female; makulární edém; laserová koagulace; kombinovaná terapie; diabetická retinopatie; výsledek terapie; ženské pohlaví; Macular Edema; lidé; vitrektomie; Treatment Outcome; Vitrectomy; retrospektivní studie; Diabetic Retinopathy; Male; Combined Modality Therapy; Aged; Laser Coagulation; lidé středního věku; senioři; mužské pohlaví; zraková ostrost; Visual Acuity; Retrospective Studies; Middle Aged; Humans